'Study like Italians do' as a migration project: field research in Togo. Issue 3 (2nd September 2017) - Zamperini, Adriano; Mascena, Alberto
ABSTRACT: In this article we present ethnographic research conducted on students taking an Italian language and culture course in Lomé, the capital of Togo. We interacted with the students and participated in their school days. In addition to the interviews, we turned to Focus Groups in order to investigate certain crucial issues. Our research reinforces the idea that migration is a strategy of living, even before surviving, thanks to which many students from West Africa can achieve their desire to learn and explore the world and gain access to higher quality education. We noted the importance of the preparatory phase, the process by which students acquire different skills needed to deal with the migration experience. 'Study like Italians do' also anticipates the scenario of the migration in the host country, which influences the expectations and behaviour that students will implement once they arrive in Italy.